2011
DOI: 10.1590/s0104-77602011000200014
|View full text |Cite
|
Sign up to set email alerts
|

Biomassa em povoamentos monoespecíficos e mistos de eucalipto e acácia-negra e do milho em sistema agrossilvicultural

Abstract: RESUMO:Objetivou-se, com este estudo, quantifi car a produção e a distribuição de biomassa da parte aérea nas plantas em povoamentos monoespecífi cos e mistos de eucalipto (híbrido E. urophylla x E. grandis) e acácia-negra (Acacia mearnsii) e do milho (Zea mays) em sistema agrossilvicultural. As avaliações de biomassa (folha, galho, casca e madeira) das espécies fl orestais, aos 6 e aos 18 meses de idade, foram realizadas nos tratamentos: 100E (100% de eucalipto + milho); -100A (100% de acácia-negra + milho); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 9 publications
1
1
0
4
Order By: Relevance
“…Sarto et al (2020d) found that establishing E. urograndis H-13 and E. grancam 1277 in pasture reduced forage yield close to the trees and that the forage yield increased along the row transect from 1.7 mg ha -1 close to trees to 4.45 mg ha -1 at 6.0 m away from the eucalyptus. Vieira and Schumacher (2011) also verified that the total biomass production of maize intercropped with monospecific and mixed plantations of the forest species did not differ between the evaluated treatments. The authors reported that the same yield between treatments could be attributed to the fact that forest species did not compete with maize as it was sown one month after the tree planting.…”
Section: Discussionsupporting
confidence: 68%
“…Sarto et al (2020d) found that establishing E. urograndis H-13 and E. grancam 1277 in pasture reduced forage yield close to the trees and that the forage yield increased along the row transect from 1.7 mg ha -1 close to trees to 4.45 mg ha -1 at 6.0 m away from the eucalyptus. Vieira and Schumacher (2011) also verified that the total biomass production of maize intercropped with monospecific and mixed plantations of the forest species did not differ between the evaluated treatments. The authors reported that the same yield between treatments could be attributed to the fact that forest species did not compete with maize as it was sown one month after the tree planting.…”
Section: Discussionsupporting
confidence: 68%
“…Apesar da sua importância, a silvicultura de espécies nativas ainda carece de informações (NASCIMENTO et al, 2012). Sobretudo, informações quanto as suas relações ecológicas, seja em plantios puros ou consorciados (BRUN et al, 2013), e referentes aos aspectos nutricionais no sistema solo-planta (VIERA & SCHUMACHER, 2011).…”
Section: Introductionunclassified
“…De forma geral, as espécies arbóreas devem ter rápido estabelecimento e as espécies agrícolas e forrageiras devem apresentar tolerância às condições do cultivo, pois a concorrência por luminosidade, água e nutrientes pode afetar sua produtividade ( VIEIRA;SCHUMACHER, 2011;VILELA et al, 2011).…”
Section: Introductionunclassified